2019
DOI: 10.1116/1.5087212
|View full text |Cite
|
Sign up to set email alerts
|

Controlled nucleation of monolayer MoSe2 islands on Si (111) by MBE

Abstract: Van der Waals bonding relaxes the constraints of lattice matching, making two-dimensional (2D) transition metal dichalcogenides attractive in the field of epitaxy. Recently, molecular beam epitaxy (MBE) of MoSe2 was demonstrated on a variety of substrates. Here, the authors use MBE to investigate the early stages of 2D nucleation of MoSe2 grown on Si in pursuit of controlled monolayer island size. The 2D nucleation rate varies by a factor of >2 over a narrow substrate temperature range of 550–560 °C. Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Remarkably, despite the significant lattice mismatch, we successfully obtain highly oriented and uniform films through van der Waals epitaxy. 3,30 The 2H phase of the MoSe 2 film is confirmed by Raman spectroscopy. Atomic force microscopy (AFM) was employed to study the surface topography of the as-grown films.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…Remarkably, despite the significant lattice mismatch, we successfully obtain highly oriented and uniform films through van der Waals epitaxy. 3,30 The 2H phase of the MoSe 2 film is confirmed by Raman spectroscopy. Atomic force microscopy (AFM) was employed to study the surface topography of the as-grown films.…”
Section: Introductionmentioning
confidence: 82%
“…22−28 However, only a few studies on MBE growth of MoSe 2 on Si(111) substrates are available in the literature. 1,3,18,29 The problem with the direct growth on Si(111), as pointed out by Ohtake and Sakuma, is the formation of the MoSi 2 phase, which prohibits further growth of MoSe 2 . 29 Xenogiannopoulou et al reported the growth of MoSe 2 on AlN(0001)/Si(111) and have shown that using the AlN template, it is possible to grow high-quality MoSe 2 films as compared to that on a bare Si substrate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The structural and electronic characteristics of (111) surfaces give rise to properties that are inaccessible to semiconductors with the traditional (001) orientation. (111)-Oriented semiconductor heterostructures are attractive for applications including topological insulators, transition metal dichalcogenides and other 2D materials, optoelectronics based on strain-induced piezoelectric effects, , and next-generation field-effect transistors. , …”
Section: Introductionmentioning
confidence: 99%